Bidirectional regulatory effects of Cordyceps on arrhythmia: Clinical evaluations and network pharmacology - Wang, Lijuan; Sun, Helin; Yang, Meina; Xu, Yulin; Hou, Linlin; Yu, Haomiao; Wang, Xueyin; Zhang, Zhongwen; Han, Jinxiang (Frontiers in Pharmacology, 2022)
Background: Cordyceps is a precious Chinese herbal medicine with rich bio-active ingredients and is used for regulating arrhythmia alongside routine treatments. However, the efficacy and potential mechanisms of Cordyceps on patients with arrhythmia remain unclear. Methods: Randomized controlled trials of bradycardia treatment with Cordyceps were retrieved from diverse databases and available data. Dichotomous variables were expressed as a risk ratio (RR) with a 95% confidence interval (CI). Continuous variables were expressed as a standardized mean difference (SMD) with a 95% CI. Network pharmacology was used to identify potential targets of Cordyceps for arrhythmia. Metascape was used for gene ontology (GO) and genome (KEGG) pathway enrichment analysis. Results: Nineteen trials included 1,805 patients with arrhythmia, of whom 918 were treated with Ningxinbao capsule plus routine drugs, and, as a control, 887 were treated with only routine drugs. Six trials reported on bradycardia and the other 13 on tachycardia. Treatment with Cordyceps significantly improved the total efficacy rate in both bradycardia (RR = 1.24; 95% CI, 1.15 to 1.35; Pz <0.00001) and tachycardia (RR = 1.27; 95% CI, 1.17 to 1.39; Pz <0.00001). Cordyceps also had beneficial secondary outcomes. No serious adverse events occurred in patients treated with Cordyceps. The results of KEGG pathway enrichment analysis were mainly connected to adrenergic signaling in cardiomyocytes and the PI3K-Akt signaling pathway. IL6, TNF, TP53, CASP3, CTNNB1, EGF, and NOS3 might be key targets for Cordyceps in the treatment of arrhythmia. Conclusion: This study confirmed that Cordyceps has a certain positive effect on the treatment of arrhythmia and that its main mechanism may be through the regulation of adrenergic signaling in cardiomyocytes and the PI3K-Akt signaling pathway.